Analysis of Communication Networks among Political Elites in the Formation of Party Coalitions - Intan Ferazia; Prayudi Prayudi; Subhan Afifi (Jurnal Ilmu Komunikasi, 2020)
The multi-party system and the limitations of the presidential threshold adopted by Indonesian democracy have encouraged political parties to coalesce with each other. This study aims to analyze communication networks and the special role of political elites in the formation of party coalitions in the 2019 Presidential Election in Indonesia. This research method adopts a communication network analysis to identify the structure of the communication network between political elites and the roles they play in relation to the formation of party coalitions for the 2019 Presidential Election. The findings indicated that the formation of party coalitions was not only due to the ideological similarities. It was also based on the existence of political profit and loss considerations in a coalition, both in targeting positions and targeting support to win the Presidential Election. Further, the experience of political actors in building relations also played an important role. The contribution of this research is in the form of recommendations for new methods of communication networks.